Nonlinear optical properties of nano-fluid and phosphate glass using z-scan technique - Shokati Mojdehi, Masoumeh (2013)
The nonlinear optical properties of aluminum oxide-chromium/nickel nano-fluids and ternary zinc-magnesium-phosphate glass (obtained from other group) were investigated in this study utilizing a single-beam Z-scan method. The nonlinear refractive index, absorption coefficient, third-order nonlinear susceptibility, and figure of merit of the samples were also measured. The nonlinear refractive indices of ethanol-based aluminum oxide-chromium nanofluids prepared with mass fraction concentrations ranging from 0.018 to 0.146 wt%, were studied. The obtained values ranged from -0.19 9 10  to -1.99 9 10  cm2/W, with negative nonlinearity. Thus, the samples exhibited self-defocusing phenomena. The nonlinear refractive index increases slowly with increasing concentration from 0.018 to 0.036 wt%, rapidly increasing from 0.036 to 0.073 wt%, and then from 0.073 to 0.146 wt%. The nonlinear absorption of the samples showed saturable absorption caused by the peak configuration at the focal point in order of 5 10 . The real and imaginary parts of third-order nonlinear susceptibility were also calculated. The value of figure of merit for each sample were calculated that satisfied the condition FOM <1. The nonlinear refractive index and absorption of ethylene-glycol-based aluminum oxide–chromium nano-fluid were investigated at mass fraction concentrations ranging from 0.013 to 0.104 wt%. The aluminum oxide–chromium nano-fluid revealed a good nonlinear behavior, with a negative nonlinear refractive index ranging from -0.30 10 10  cm2/W to -2.86 10 10  cm2/W. This nonlinearity increased linear gradually with an increasing concentration of sample. Furthermore, the nonlinear absorption behavior showed a saturable absorption caused by the peak configuration at the focal point. The magnitudes of figure of merit for the sample were calculated that satisfied the condition FOM<1. The nonlinear optical properties of ethanol-based aluminum oxide-nickel nano-fluid at different mass fraction concentrations ranging from 0.018 to 0.146 wt% were characterized. A negative nonlinear refractive index was obtained, and a self-defocusing phenomenon was observed at 405 nm from -1.36 9 10  to -3.41 9 10  cm2/W. The nonlinear refractive index was increased approximate linearly (moderate trend). In case of open aperture transmittance data, no nonlinear behavior was observed in the absorption coefficient. Furthermore, the real part of third-order nonlinear susceptibility was presented in order 10-6 that depended on nonlinear refractive behavior of aluminum oxide- nickel nano-fluid. The nonlinear optical properties of a phosphate glass system [(ZnO)x–(MgO)30-x– (P2O5)70], where x = 8, 10, 15, 18 and 20 mol%, with synthesized melt-quenching (obtained from other group) were investigated. In this experiment, a 405 nm CW laser was operated to determine both the sign and value of the nonlinear refractive index and absorption coefficient. The nonlinear refractive index was found to vary from 0.45 10 10  to 2.11 10 10  cm2/W. The nonlinear refractive index value increased with increasing ZnO concentration in the glass samples. From the measurement, the positive nonlinear refractive index demonstrated self-focusing phenomenon. The nonlinear absorption behavior showed reverse saturable absorption caused by the valley configuration at the focal point. The value of figure of merit was presented to attribute the potential of the samples for utilizing in optical switching by following condition FOM <1. The nonlinear optical properties of phosphate glasses in [(ZnO)30- (MgO)x– (P2O5)70-x] (x = 5, 8, 13, 15 and 20 mol%) glassy system (obtained from other group) were investigated. The magnitude and the sign of nonlinear refractive index and nonlinear absorption coefficient were obtained from the closed and open aperture data, in which the magnitude of nonlinear refractive index ranged from 1.82 10 10  to 7.92 10 10  cm2/W that the nonlinear refractive index increased. The glass samples demonstrated self-focusing phenomenon, as shown by the positive nonlinear refraction of index. The figure of merit for the sample were also calculated that satisfied the condition of FOM<1 to use in optical devices.